Seasonal dynamics of Galaxea fascicularis holobiont from physiological to transcriptional responses and implications for natural resilience - Li, Yushan; Ke, Jingzhao; Yang, Haiyan; Liu, Xiangbo; Zhang, Junling; Huangfu, Mingce; Liu, Jinling; Zhu, Wentao; Wang, Aimin; Chen, Rou-Wen; Li, Xiubao (Frontiers in Microbiology, 2025)
Monitoring seasonal changes in coral holobionts throughout the year is essential for understanding coral resilience and symbiotic responses. Previous studies have focused on short-term or specific seasonal changes, limiting their ability to capture annual variations. This study on Galaxea fascicularis in the South China Sea integrates physiological, symbiotic, and transcriptomic analyses across all seasons. In spring, upregulation of Symbiodiniaceae photosynthetic genes and lipid synthesis genes enhances coral photosynthesis and lipid accumulation, promoting growth and reproduction. During July–September, seawater temperatures at the Wuzhizhou Island approached the coral bleaching alert level 2. Summer heat stress reduced photosynthetic capacity, shifted corals to heterotrophy (Δh-z 13C < 0), and increased MDA content threefold. Signaling pathways, antioxidant systems, and immune pathways were activated. Coral recovery began in autumn and winter after the summer heat and reproduction. In autumn, autotrophy increased, and immunity was activated to repair oxidative damage. In winter, processes for skeleton growth, energy storage, and metabolism were enhanced. Endosymbiotic Durusidinium remained stable, while Endozoicomonas abundance decreased in summer. In winter, potential pathogenic bacteria like Acinetobacter increased. These findings highlight the coral holobiont’s synergistic response to seasonal changes, validating coral resilience and guiding artificial restoration strategies.